2006
DOI: 10.1161/01.str.0000196939.12313.16
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term Mortality in Patients With Ischemic Stroke Referred for Transesophageal Echocardiography

Abstract: Background and Purpose-Findings on transesophageal echocardiography (TEE) after ischemic stroke predict recurrent embolic events and prompt therapy; however, the additive predictive power of TEE findings on long-term mortality is unknown. Our goal was to study the impact of TEE findings on all cause mortality in ischemic stroke patients referred for TEE. Methods-We reviewed 245 consecutive patients who underwent TEE for ischemic stroke of undetermined origin (2000 to 2003). Long-term survival was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
4
16
0
1
Order By: Relevance
“…Although the presence of "complex" AA (ulcerated plaques, mobile plaques) is a powerful predictor of ischemic stroke [17], its role in the prediction of other cardiovascular events is controversial [18]. In agreement with the study of Ward et al [18], highgrade AA predicted survival in our study. However, only diabetes and CFR independently predicted survival.…”
Section: Discussionsupporting
confidence: 82%
“…Although the presence of "complex" AA (ulcerated plaques, mobile plaques) is a powerful predictor of ischemic stroke [17], its role in the prediction of other cardiovascular events is controversial [18]. In agreement with the study of Ward et al [18], highgrade AA predicted survival in our study. However, only diabetes and CFR independently predicted survival.…”
Section: Discussionsupporting
confidence: 82%
“…An apparently obvious explanation for the independent relationship between HF and poor outcome in stroke patients may be related to its underlying causes: atherosclerotic coronary disease, hypertensive disease, and valvular disease. These factors are associated with a higher atherosclerotic burden [26], endothelial dysfunction [13], more complex treatments, and a higher risk of death [22] or systemic-embolic complications [9]. However, these considerations are present in both conditions of HF.…”
Section: Discussionmentioning
confidence: 99%
“…18 -21 Additionally, we have previously reported that complex aortic plaques are the only individual CSE found on TEE after ischemic stroke to be associated with an increased mortality. 11 We included complex aortic plaques in all thoracic locations in our definition of a positive TEE finding because we felt this definition was relevant to clinical practice. Although the evidence that descending aortic atheroma can cause central nervous system events is limited, 22,23 studies addressing prognostic and therapeutic implications of complex aortic atheroma found on TEE after embolic events have included plaques in all thoracic locations.…”
Section: Discussionmentioning
confidence: 99%